Analysis of Real Costs and INA-CBG of Hyperthyroidism in Hasanuddin University Hospital - Abdullah, Siti Saharah; Lorensia , Amelia; Suyanto (Media Kesehatan Masyarakat Indonesia, 2020)
Hyperthyroid disease requires continuous treatment with not cheap medical costs. For JKN participants, the cost of treating hyperthyroidism has been fully covered by BPJS through the INA-CBG package. However, there is often a mismatch between the INA-CBG package and the real hospital costs thus causing losses for the hospital. This research is a comparative study with a hospital perspective and the purpose of this study is analyze difference between direct medical cost of hospitals and INA-CBG package for the treatment of JKN outpatient hyperthyroidism patient in Hasanuddin University Hospital (RSUH) Makassar using data from January 2017 to December 2018. Data collection was carried out by retrospective observational and data analysis using statistical non- parametric tests. The results showed that INA-CBG package cannot cover all components of the costs of treating hyperthyroid disease. The laboratory cost has a proportion of 83% of the total medical cost, which is an average of IDR 465.683,70 every patient. Meanwhile, the INA-CBG rate with code Q-5-44-0 only covers medical expenses of IDR 185.500 every patient. The conclusion of this study shows that there is a negative difference (-) between the real cost of the hospital and the INA-CBG rate, which is IDR 34.406.900,00 and an average of IDR 373.988.04 every patient. The recommendation is related to adjustment of the INA-CBG rate to cover the riil costs.